Short-term training programs for immigrants in the German welfare system: Do effects differ from natives and why? - Stephan L. Thomsen; Thomas Walter; Alisher Aldashev (IZA Journal of Migration, 2013)
We evaluate the individual employment effects of four types of short-term training for immigrants and natives in the German welfare system and identify differences in the effects determined by unobservable factors. Based on comprehensive and unique administrative data, we apply propensity score matching in a dynamic setting to estimate the treatment effects and suggest the identification of unexplained effect differences between groups. The results show a mixed picture: two types of training increase the employment chances of immigrants, whereas the other two are rather ineffective. Effect differences between immigrants and natives predominantly result from socio-demographic composition.
Keywords: I38; C14; J61; 330; Immigrants; Welfare; Short-term training; Evaluation; Immigrant fixed effect